ASSESSING COMMON GENETIC AND ENVIRONMENTAL EFFECTS ON THE ASSOCIATION BETWEEN PARENT-CHILD RELATIONS AND INTIMATE PARTNER RELATIONSHIP QUALITY (Journal of actual problems of jurisprudence, 2020)
The current study examined the genetic and environmental architecture of early life parent-childrelations and intimate partner relationship quality later in life. A series of univariate ACE and bivariateCholesky decomposition models were fitted to a sample of monozygotic and same-sex dizygotic twinsdrawn from the Midlife in the United States Study (MIDUS) in order to explore the extent to whichgenetic factors explain individual differences in mother- and father-child relationship quality and selfreportsof intimate partner relationship quality. Results revealed that genetic factors explained variationin reports of parent-child relationship quality (41% to 65%), adult intimate partner relationship quality(34%) and the covariance between the two (81% to 83%). Nonshared environmental factors accountedfor the remaining covariance. Findings from the present study suggest that similar genetically influencedcharacteristics that account for variation in early life parent-child relations are also implicating in explainingvariation in healthy intimate partner formation later in life. The implications of these findings forfuture research on intimate partner relationship quality and family formation are discussing.Key words: parent-child relations, intimate partner relationship quality, behavioral genetics, adultrelationships.